Effect of a suite of aggression management modules on health professions student knowledge, skills and confidence: an investigator-blinded, parallel-group randomised controlled trial protocol - Lau, Steven; Recoche, Katrina; Fairhall, Robyn; Gosling, Cameron; Hayman, Bernadette; Lentin, Primrose; Snipe, Jim; Turner, Shelley; Wright, Caroline; Ford, Allie; Lo, Kristin (International Journal of Clinical Trials, 2021)
Background: Incidents of aggression are increasing in healthcare. Students are at higher risk of being on the receiving end of client aggression due to their lack of experience. Students also do not feel prepared to manage these situations. Methods: Students of health professions in the School of Primary and Allied Health Care will be eligible and contacted within lectures/via the learning management system Moodle. A randomised controlled trial (RCT) will be conducted to evaluate a suite of online aggression management modules for health professions students prior to entering their clinical years of study. If students are able to undertake face to face simulations they will be assessed by academic staff members using the English modified de-escalating aggressive behaviour scale (EMDABS). Mock clients will assess the students using the consultation and relational empathy (CARE) measure. Students will complete a self-assessment using the confidence with coping with patient aggression instrument and a knowledge questionnaire. Conlusions: This RCT will provide novel information on the effectiveness of delivering a suite of online aggression management modules to health professions students. There are three separate modules each of approximately 30 minutes duration such that the attention of students is maintained. The three modules are: 1. Recognising and preventing aggression-the basics, 2. Responding to aggression-the basics, 3. Aggression in healthcare-the basics (Case study). Trial registration number: This trial has been registered with the Australian and New Zealand clinical trials registry (ANZCTR) ACTRN12621000382875.